Pengaruh Screen Time terhadap Motivasi Belajar Siswa Sekolah Dasar - Romi Fadila; Taufiq Hidayat; Sapto Wibowo (Jurnal Porkes, 2026)
Excessive use of digital devices among elementary school children is a worrying problem because it has the potential to interfere with learning motivation. This study aims to determine the effect of screen time on the learning motivation of sixth grade students. This study uses a quantitative approach with a correlational survey design. The research sample consisted of 32 students determined by random sampling technique. Data collection used a Likert scale questionnaire to measure screen time and learning motivation. Data analysis was performed using Pearson's correlation test and multiple linear regression with the help of SPSS version 25. The results showed that screen time had a significant negative effect on learning motivation. Weekday screen time was strongly negatively correlated with learning motivation (r = -0.81; p < 0.05), and weekend screen time showed an even stronger correlation (r = -0.86; p < 0.05). Regression tests revealed that every 1-hour increase in weekday screen time reduced learning motivation by 2.15 points, while weekend screen time reduced it by 3.08 points. Simultaneously, screen time contributed 79% to the variation in learning motivation. The conclusion of this study confirms that excessive screen time, especially on weekends, has a negative impact on the learning motivation of elementary school students.